Studies on the Use of Oyster, Snail and Periwinkle Shells as Adsorbents for the Removalof Pb2+ Aqueous Solution - Stevens A. Odoemelam; Nnabuk Okon Eddy (E-Journal of Chemistry)
In view of increasing rate of lead pollution resulting from discharge of lead containing effluents by industries into the environment, this study was carried out to investigate the removal of Pb2+ from aqueous solutions by oyster, snail and periwinkle shells. The effects of contact time and concentration on adsorption, thermodynamics of sorption and distribution coefficients of the adsorbents were examined to optimize the conditions to be utilized for decontamination of effluents containing Pb2+. The study revealed that these materials are good adsorbents that can be used for the removal of Pb2+ from aqueous solution. Adsorption of Pb2+ by oyster, snail and periwinkle shells were found to conform to the classical models of Langmuir, Freundlich and Temkin adsorption isotherms. Thermodynamic consideration revealed that adsorption of Pb2+ by these materials was spontaneous and proceeded via chemical adsorption. The use of these materials for the removal of lead ion from aqueous solution is therefore advocated